Industrialized Building System: Shift of Massive Reliance on Foreign Workers to Greater Automation - Loke, Suek Yin (2020)
Industrialized Building System (IBS) is a modern method of construction which utilizing advanced technology to save the labour workforce and boost the productivity of works. In light of Malaysian construction industry massively reliance on the foreign workers, it is not only affected construction industry, but also induced negative impacts to social and economy. Hereby, the purpose of this research is to study the shifting of massive reliance on foreign construction workers to greater automation through adoption of IBS in Malaysian construction projects. This research intends to study the factors of reliance on the foreign construction workers, identify the attributes of IBS in saving foreign labours workforce and investigate the effectiveness of IBS in reducing the foreign workers. Questionnaire forms were delegated to G7 IBS contractors registered under CIDB to facilitate the data collection. The data was analysed by using descriptive analysis such as mode, frequency and percentage. Relative Importance Index (RII) is also used to analyse the Likert scale questions to rank the importance of the data being collected. The results of the study show that IBS is efficiently reduce the numbers of worker on site up to 40% and successfully shifting the reliance on foreign workers from high level to low level. Pushing the adoption of IBS among construction players is significant to shift the reliance on foreign workers towards greater automation as well as transform Malaysian construction industry into new revolution.